Selection of volleyball players using fuzzy PROMETHEE / Khairunnisa Anuar - Anuar, Khairunnisa (2020)
One of coaches' roles is to select players. However, selecting players is not an easy task. This is because there are many criteria that need to be considered and because a coach's judgement is subjective. This study seeks to determine the most important criterion in selecting volleyball players and to rank volleyball players in order to do the selection. In this study, twelve MAKSAK Perlis volleyball players were evaluated based on six basic volleyball skills namely serving, setting, spiking, blocking, digging and receiving. Two coaches were responsible in doing the evaluation of players for this study. A fuzzy multi-criteria decision making method called fuzzy PROMETHEE was used in this study to rank the players. The result showed that the most important criteria in selecting volleyball players are serving, spiking and digging. The twelve players were successfully ranked and the result of the ranking allowed the selection of players to be made. The result of the ranking also allowed the main players and reserved players to be determined. This study showed that fuzzy PROMETHEE can be used as a practical method for coaches to select players.